PEMBAHARUAN DALAM ANALISIS KIMIA MAKANAN: PENENTUAN LOGAM BERAT DALAM MAKANAN (TEMU ILMIAH NASIONAL PERSAGI, 2023)
During the last decade, the increasing demand of food safety has stimulated research related to the risk associated with consumption of food stuffs contaminated by heavy metals. The implication associated with heavy metal contamination is of great concern. Heavy metals, in general are not biodegradable, having long biological half-lives and having the potential for accumulation in the different body organs leading to unwanted side effects. Heavy metals have positive and negative effects on the human health, it can be classified as essential for biochemical reactions in the body (copper, iron, zinc, etc.) and potentially toxic (lead, cadmium, arsenic, mercury etc.). Therefore, the assessment of metals in foods are necessary since food intake is a main path of metals entered human body. Several research related to metal contents in foods as well as in human’s diet have been conducted. Nuclear analytical techniques offer simultaneous, high selective and sensitive analytical methods, suitable to characterize metals in various samples including foods. There are several findings related to heavy metal in foods i.e., high concentration of certain heavy metals has been identified in several foodstuffs from Jakarta traditional markets. High potential risk of heavy metal contaminant was also found in street vended foods collected from school areas in Bandung city. The heavy metals in foods may also strongly correlated with the environmental pollution. Several case studies regarding to the issues have been carried out. From edible plant samples collected around vicinity area of industrial activity, the concentration of heavy metals has been found significantly high. These results are the scientific evidence that heavy metal contaminated foods may present in every place, and should increase the awareness of the related parties as well as public. Despite of essential elements deficiency, heavy metal accumulation in the body also played important contribution to the malnutrition problems in Indonesia. In conclusions, reducing heavy metal contents in foods is strongly attributed on the quality of the environment.